2000
DOI: 10.1128/jb.182.14.4035-4043.2000
|View full text |Cite
|
Sign up to set email alerts
|

Integration and Excision of a Bacteroides Conjugative Transposon, CTnDOT

Abstract: Bacteroides conjugative transposons (CTns) are thought to transfer by first excising themselves from the chromosome to form a nonreplicating circle, which is then transferred by conjugation to a recipient. Earlier studies showed that transfer of most Bacteroides CTns is stimulated by tetracycline, but it was not known which step in transfer is regulated. We have cloned and sequenced both ends of the Bacteroides CTn, CTnDOT, and have used this information to examine excision and integration events. A segment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
129
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(131 citation statements)
references
References 34 publications
2
129
0
Order By: Relevance
“…In vitro cleavage assays using phosphorothioate substrates revealed that the cleavage site on the top strand was located two bases to the left (between the T and G) within the 10-bp region of homology. Thus, the cleavage sites for IntDOT are 7 bp apart, and the attDOT-and attB-site overlap regions share 2 bp of identity on the left side (19,49) (Fig. 4).…”
Section: Tyrosine Recombinases That Violate the Homology Rulementioning
confidence: 99%
See 2 more Smart Citations
“…In vitro cleavage assays using phosphorothioate substrates revealed that the cleavage site on the top strand was located two bases to the left (between the T and G) within the 10-bp region of homology. Thus, the cleavage sites for IntDOT are 7 bp apart, and the attDOT-and attB-site overlap regions share 2 bp of identity on the left side (19,49) (Fig. 4).…”
Section: Tyrosine Recombinases That Violate the Homology Rulementioning
confidence: 99%
“…4). Originally, the coupling sequences were thought to be 5 bp in length, since only five bases varied between sites (19). In vitro cleavage assays using phosphorothioate substrates revealed that the cleavage site on the top strand was located two bases to the left (between the T and G) within the 10-bp region of homology.…”
Section: Tyrosine Recombinases That Violate the Homology Rulementioning
confidence: 99%
See 1 more Smart Citation
“…Some ICE families target a single specific attachment site in the bacterial chromosome, usually in a tRNA gene (45), suggesting that these plasmids have evolved a strategy to avoid arbitrary disruption of the host genome during integration. However, other ICE families target multiple attachment sites (46), and some families, like Tn916, integrate almost randomly in the host chromosome (47). This nonspecific integration can disrupt protein coding or regulatory regions or can interfere in the expression of genes flanking the integration site, entailing fitness costs in the recipient bacterium.…”
Section: Plasmid Integrationmentioning
confidence: 99%
“…Using an unrelated suicide vector, pGW161.1, which carried ermG, a single-crossover disruption was introduced into the integrase gene (attR side) of the oriT gene of the CTnERL element in BT4104⍀traP, generating the doubleinsertion strain BT4104⍀traP⍀int. All gene disruptions were tested by PCR (⍀int) and/or Southern blot analysis (⍀traP) to confirm that the single-crossover insertions resulted in the expected gene disruption or phenotype as described previously (2,4,5). No excision was detected by PCR amplification of the joined ends of the mutant element, demonstrating that the insertion in intERL had indeed eliminated normal excision.…”
mentioning
confidence: 99%